2014
DOI: 10.1007/s11571-014-9303-3
|View full text |Cite
|
Sign up to set email alerts
|

MMN responses during implicit processing of changes in emotional prosody: an ERP study using Chinese pseudo-syllables

Abstract: In this study, we tested the underlying mechanisms of early emotional prosody perception, especially examined whether change detection in oddball paradigm was caused by emotional category and physical properties. Using implicit oddball paradigms, the current study manipulated the cues for detecting deviant stimuli from standards in three conditions: the simultaneous changes in emotional category and physical properties (EP condition), change in emotional category alone (E condition), and change in physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
(57 reference statements)
3
16
0
Order By: Relevance
“…Source estimations during the MMN onset temporal window (190-230 ms) across all conditions showed activations in the right insulo-temporal region and the left fronto-parietal region. Right-lateralized temporal activations are in line with previous MMN studies that reported right activations for pitch deviants in tones and voice (Jiang et al, 2014;Lappe et al, 2016). In addition, the right anterior insula is involved in processing vocal emotions Belin et al (2004), and has also been associated to MMN responses to emotional syllable deviants (Chen et al, 2014b).…”
Section: Source Activationssupporting
confidence: 89%
“…Source estimations during the MMN onset temporal window (190-230 ms) across all conditions showed activations in the right insulo-temporal region and the left fronto-parietal region. Right-lateralized temporal activations are in line with previous MMN studies that reported right activations for pitch deviants in tones and voice (Jiang et al, 2014;Lappe et al, 2016). In addition, the right anterior insula is involved in processing vocal emotions Belin et al (2004), and has also been associated to MMN responses to emotional syllable deviants (Chen et al, 2014b).…”
Section: Source Activationssupporting
confidence: 89%
“…Some previous MMN studies conducted in adults have also reported an effect of emotion on MMN amplitude (Jiang et al, 2014;Pakarinen et al, 2014;Schirmer et al, 2005), whereby the emotional MMN was larger than the neutral MMN. However, potential low-level modulators of the MMN were not always controlled in these studies.…”
Section: Brain Responses To Prosodic Changes In Adultsmentioning
confidence: 76%
“…MMN studies using vocal stimuli in adults suggest an early integration of emotional prosodic change. Comparing the neutral and emotional MMNs elicited by syllables or pseudowords, studies with various paradigms (oddball, optimum, or control sequences) evidenced a larger MMN amplitude for emotional (happy, angry, sad) than for neutral change (Jiang, Yang, & Yang, 2014;Pakarinen et al, 2014;Pinheiro, Barros, Vasconcelos, Obermeier, & Kotz, 2017;Schirmer, Striano, & Friederici, 2005). Emotional change detection is also characterized by an earlier MMN in studies using syllables (Schirmer et al, 2005), interjections (Schirmer, Escoffier, Cheng, Feng, & Penney, 2016), vocalizations (Pinheiro et al, 2017), or pseudowords (Thönnessen et al, 2010).…”
mentioning
confidence: 95%
“…In fact, human beings are geared to quickly recognize emotion change in vocal expressions. For instance, it was found that deviant emotional notes, which lead to emotion change in oddball paradigm, elicited early negative responses (MMN) around 200 ms in passive condition (Goydke et al 2004;Jiang et al 2014;Schirmer and Escoffier 2010;Schirmer et al 2008;Schirmer et al 2005;Thonnessen et al 2010). In contrast, deviant emotional notes elicited a late positive deflection (P300) in active oddball paradigm (Thierry and Roberts 2007;).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, though the ERP data in previous studies (Chen et al 2011;Jiang et al 2014;Wambacq and Jerger 2004) effectively depicted the time course of processing emotional change information, the acquisition of ERP data is exclusively restricted to phase-locked averaging (Luck 2005;Pfurtscheller and da Silva 1999). In contrast, timefrequency analysis provides non-phase-locked indexes of cognitive processing, and thus delineates the neural oscillatory dynamics, an inherent characteristic of synchronizing or desynchronizing ongoing activity in various frequency bands Neuper and Klimesch 2006;Pfurtscheller and da Silva 1999).…”
Section: Introductionmentioning
confidence: 99%